DESAIN OTONOMI DAERAH DALAM KERANGKA PENEGASAN SISTEM PEMERINTAHAN PRESIDENSIAL - Rio Armanda Agustian (PROGRESIF: Jurnal Hukum, 2018)
This research is entitled “Design Of Regional Autonomy In The Affirmative Framewok Of Presidential Government Systems Affirmation:. This research is motivated by the decentralization of Indonesia which has unsymmetrical, because of the existence of specific nd special regions, further more in terms of the presedential government system there is a problem in the development of its subsystems up to regional government. Thus, understanding is needed to understand th reality and redesign of regional autonomy in regional head elections, specific and special regions, and in order to reaffirm the presidential government system in an effort to build relations between the president and regional heads. As for the method used in making this writing is a juridical method normative or doctrinal. Design Of Regional Autonomy In The Affirmative Framewok Of Presidential Government Systems, By Rio Armanda Agustian. Abstract this research is entitled Design Of Regional Autonomy In The Affirmative Framewok Of Presidential Government Systems Affirmation. This research is motivated by the decentralization of Indonesia which has symmetricity, namely the existence of special and special regions, then if viewed from the presidential government system there is a problem in the development of its subsystems to regional government. Thus, understanding is needed to nderstand the reality and redesign of regional autonomy in regional head elections, special and special regions and in order to reaffirm the presidential government system in an effort to built relations between the president and regional heads. As for the method used in making this writing is a juridical method normative or doctrinal, because the data search is done by reviewing local government law and legislation related., and the data also related to the privilege and specificity of the region. The results of this study is themiddle solution to solve the problem can also be done by direct appointment of the governor by the president, although this is very unpopular and very risky politically, but if it starts with rational reasons, surely the people in the area will accept, and of course with a low cost as well. The direct appointment is very necessary for the president so that relations with the governor as an extension of president’s hand will be stronger.